Editorial: Internationalisation of Higher Education and Entrepreneurship Education - Pasierbek, Wit; Pera, Bożena (Horyzonty Wychowania, 2020)
Alongside performing their traditional functions of educating and conducting research, contemporary universities face a range of new challenges. One of them is to become more involved in the process of social and economic development, which can be achieved by e.g. establishing fruitful relations with the business sector. The changes that address this need are connected with the implementation of the concept of an entrepreneurial university. The aim of such university is to educate future employees able to meet the expectations of the labour market not only in the area of specialised professional knowledge but also in the area of skills, competences, and entrepreneurial attitudes. Entrepreneurship education – offered at its different levels – is one of the most significant challenges of the contemporary education system. Entrepreneurship education shapes entrepreneurial competences, skills and attitudes through various forms of education, activating teaching methods and aids that increase students’ involvement in the teaching and learning process. Communication and information technologies are increasingly used in the entrepreneurial approach to learning to support its implementation.